The influence of controlled fires on a vegetation community in the south of the Caldenal and its relationship with a regional model of states and transitions - Tizón, Francisco Rodrigo (2010)
Fire plays a fundamental role in the composition and structure of vegetation communities in the Caldenal, however this effect has decreased notably since the introduction of domestic cattle due to the reduction of fine combustible material. The aim of the present study was to analyse the diversity and composition of a typical vegetation community in the south of the Caldenal exposed to different fire frequencies and to show the convenience of the use of controlled fire for reversing the processes of scrub formation to states with more diverse and productive grassland. Forty-five herbaceous and woody species were recorded. Treatment C (control) showed the greatest richness and diversity for December 2006 and 2007. After the last controlled fire the compostition of the vegetation community differed significantly between treatment C and treatments T1 and T2 (with burns every 3-4 and 7-8 years respectively). This change is mainly due to the proliferation of palatable perennial grasses. The vegetation composition of the same treatments, for both dates in 2006 and 2007, was similar for C and T2 (ANOSIM, R=0.01, p=0.32 y R=0.06, p=0.01, respectively). However, treatment T1 showed significant changes (ANOSIM, R=0.42, p=0.01). Nasella clarazii, which is characteristic of the palatable grasses in the region, was the perennial forage grass with greatest cover in treatment T2,  whereas it was scarce in treatments C y T1. Unpalatable grasses and bushes grow at sites without fire, e.g. treatment C in this study, and so it is seen that the use of controlled fire of intermediate frequency would favour the aerial cover of palatable perennial grasses in those states that are most useful for sustainable cattle production.